2001
DOI: 10.1348/014466501163715
|View full text |Cite
|
Sign up to set email alerts
|

The Challenging Behaviour Scale (CBS): Development of a scale for staff caring for older people in residential and nursing homes

Abstract: The CBS is quick to complete and may have potential for the evaluation of psychosocial interventions in care settings. It is, as far as we know, the first staff observational rating scale that is based on the reports of care staff, who constitute the backbone of residential care provision. Suggestions for improvements in criterion and content validity are outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 28 publications
1
43
0
Order By: Relevance
“…Hoe et al (2006) found behavioural disturbance as measured by the Clifton Assessment Procedures for the Elderly Behavioural Rating Scale (CAPE-BRS; Pattie et al, 1978) to be highly correlated with staffratings of the QOL-AD but not self-ratings (À0.53, compared with 0.00). The results from the Challenging Behaviour Scale (CBS; Moniz-Cook et al, 2001) were very similar with staff-rated decreased patient quality of life associated with increasing challenging behaviour (À0.40) but not in self-ratings (À0.14). In severe dementia, Hoe et al (2005) reported no statistically significant correlations between self-rated QOL-AD score and NPI total score (À0.11), with only its apathy subscale associated with decreased quality of life (À0.40).…”
Section: Behavioural Disordermentioning
confidence: 79%
“…Hoe et al (2006) found behavioural disturbance as measured by the Clifton Assessment Procedures for the Elderly Behavioural Rating Scale (CAPE-BRS; Pattie et al, 1978) to be highly correlated with staffratings of the QOL-AD but not self-ratings (À0.53, compared with 0.00). The results from the Challenging Behaviour Scale (CBS; Moniz-Cook et al, 2001) were very similar with staff-rated decreased patient quality of life associated with increasing challenging behaviour (À0.40) but not in self-ratings (À0.14). In severe dementia, Hoe et al (2005) reported no statistically significant correlations between self-rated QOL-AD score and NPI total score (À0.11), with only its apathy subscale associated with decreased quality of life (À0.40).…”
Section: Behavioural Disordermentioning
confidence: 79%
“…Challenging Behaviour Scale (CBS) (Moniz-Cook et al, 2001). A 25-item checklist that rates the frequency and severity of challenging behaviour presented by older people with dementia with higher scores indicating more problematic behaviour.…”
Section: Instrumentsmentioning
confidence: 99%
“…The Challenging Behaviour Scale (CBS) was developed to meet the need for a measure of resident behaviours that formal caregivers in long-term care facilities find difficult to manage (Moniz-Cook et al, 2001). It defines challenging behaviour as 'behaviour of such an intensity, duration or frequency, that the physical safety of the person or another is placed in serious jeopardy, or behaviour which is likely to seriously limit or deny access to ordinary community facilities' (Emerson et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The challenging behaviours can be explained by a behavioural model that encourages the analysis of staff/client interactions and the implementation of behavioural modification programmes (Harborne and Solly, 1996). The strength of the CBS is that it covers both global and specific behaviours in residents with dementia such as lack of occupation, agitation, aggression, eating and sleep problems (Moniz-Cook et al, 2001). It describes the challenging behaviours in common language and incorporates a measurement of 'challenge' (MonizCook et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation